Qualidade de vida em pacientes com psoríase: relação com comorbidades, severidade dos casos e nível de conhecimento sobre a doença - Trabold, Luciana Andreia (2017)
Introduction: The impact of psoriasis on the quality of life reaches objective domains and also domains depending on perception. A fair evaluation on life quality must take into account the level of patients’ awareness related to their disease. Objective: To contribute for the studies of life quality in patients with psoriasis, evaluating this in patients from Policlínica Municipal – Unisul in Palhoça, Santa Catarina, Brazil and, to correlate data of severity, comorbidities and level of knowledge of the disease. Methods: A questionnaire was created for the investigation evaluating anthropometry, demographic and socioeconomic aspects, life style and history of psoriasis and comorbidities in 115 adult patients. This was supplemented by the instruments Psoriasis Disability Index, Psoriasis Area and Severity Index and Patient Awareness in Psoriasis (PAP). Results: The average interviewee was about 53 years old and had nutritional excess, with some level of sedentary lifestyle, most of them presenting comorbidities (<80%), mainly components of the metabolic syndrome or depression. The average quality of life impairment was about 30%, being increased in patients with severe cases (<45%). The increase in body mass index was related to an increase in quality of life impairment. PAP mean value in this sample was 49.5 ± 15,2%. Patients with a better knowledge of their disease reported higher quality of life impairment, as well as patients with more severe cases. Conclusion: The patient with psoriasis needs attention transcending their physical needs and considering the risk of cardiovascular diseases. Educational approaches are valid, since the aggravating factors of the quality of life of these patients are often reversible.